Modelling of simultaneous encapsulation of betacyanins and antioxidant during spray drying of red amaranth extract - Chong, Pik Han; Aziz, Mohammad Gulzarul; Yusof, Yus Aniza; Naim, Mohd Nazli; Ching, N. L.; Mohd Rosdan, Faridatul Ain (Faculty of Engineering, Universiti Putra Malaysia, 2012)
Amaranth betacyanin, responsible for red or violet color was extracted from Amaranthus gangeticus by using water extraction method and microencapsulated by spray drying. The physicochemical, and nutritional properties of microencapsulated betacyanins were assessed as influenced by inlet temperature and maltodextrin concentration. The process was conducted on a mini spray dryer and maltodextrin was used as encapsulating agent. Central composite design was used and thirteen experiments were carried out. The responses were betecyanin retention, moisture content, water activity, particle densities, particle size, colour values and antioxidant activity. Quadratic effect of inlet temperature was found positive on betacyanin retention whereas antioxidant was affected by linear change of maltodextrin. Moisture content and water activity are hardly affected by inlet temperature and maltodextrin concentration individually. Only the effect maltodextrin concentration was found significant on color value. Particle densities and sizes are slightly affected by the process conditions studied.